A Study of the Determinants of Inbound Tourism in Hong Kong from 1998 to 2009 - Zhang, Le (Université d'Ottawa | University of Ottawa, 2012)
This paper identifies the determinants that contribute to tourism demand in Hong Kong. Annual data from 20 major origin countries or territories during the period of 1998 to 2009 are used to study tourism demand with panel data models. Since tourism in Ho